PENGGUNAAN AKAD MURABAHAH DALAM PEMBIAYAANMODALUSAHA PADA PT. PERMODALAN NASIONAL MADANI MEKAAR SYARIAH CABANG KUANTAN MUDIKBERDASARKAN HUKUM EKONOMI SYARIAH - Pela Sapira; Mardalena Hanifah; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
This reseach the use of Murabahah Contracts at PT. Mekaar Syariah National CivilCapital, hereinafter referred to as PNM Mekaar Syariah Kuantan Mudik in business capitalfinancing. The use of a murabaha contract that is not carried out in accordance with theprovisions of the Sharia Economic Law. Therefore, it is necessary to study first, how is the useof the Murabahah Contract in financing venture capital at PT. National Capital MadaniMekaar Branch of Kuantan Mudik based on Sharia Economic Law. Second, is the contract thatshould be used in financing venture capital at PT. National Civil Capital Mekaar SyariahMudik Strength Branch.This research is a sociological legal research, with the intention of looking at thecorrelation between law and society. Because it is based on field research, namely by collectingdata from observations, interviews, questionnaires, and literature studies that have to do withproblems using qualitative data analysis, producing descriptive data, and concluded with adeductive thinking method.From the results of the study, it was concluded that, First, in the PNM Mekaar SyariahKuantan Mudik Branch agreement with customers, financing is given in the form of money inthe amount according to the financing application submitted by the customer so that the saleand purchase between PNM Mekaar Syariah Kuantan Mudik and the customer does not occur,then the customer is given the authority to use the financing money to buy goods according tobusiness needs, but in practice the customer does not exercise this power and uses the financingmoney for other purposes such as consumptive needs. Second, the implementation of financingcarried out by PNM Mekaar Syariah Kuantan Mudik which provides financing in the form offunds, is more appropriate to use a musyarokah contract because the provision of businesscapital in the form of money is not appropriate using a murabaha sale and purchase scheme,but business capital financing transactions in the form of money are more appropriate to use acontract. musyarakah agreement.Key Words : Financing, Murabahah, sharia economy